Pabco's Linoleum Mural
Pabco's Linoleum Mural is a striking feature of the exhibit that The Paraffine Companies, Inc., has in the Homes and Gardens Building - and one of the major spectator-magnets of the 1939 Golden Gate International Exposition. The unique all-linoleum mural depicts "the Evolution of Shelter" from pre-historic times to 1939, in a dramatic twenty-eight foot panorama. Twenty-seven different patterns of world-famous Pabco linoleum were used in fashioning this colorful art-craft masterpiece. Modern bold-stroke technique and striking color contrasts give a strong cadence and eloquent simplicity to the Shelter Parade Through the Ages, as follows: 1. A prehistoric cave dwelling 2. A lake hut not far removed from the tree dwelling era 3. A "First American" home, or Indian wigwam 4. Log cabin of the frontier period 5. New England colonial home 6. Early California Spanish bungalow 7. "Gay Nineties" gingerbread house 8. The home of 1939.